The Gilded Age, Part 3. - Twain, Mark, 1835-1910; Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Gilded Age, Part 3." by Mark Twain and Charles Dudley Warner is a satirical novel published in 1873. It follows a poor rural family's attempts to gain wealth by selling their vast land holdings, while their adopted daughter Laura becomes a Washington lobbyist seeking congressional support. A parallel story tracks two young men pursuing fortune through land speculation. The novel satirizes the greed, corruption, and social pretensions of post-Civil War America, ultimately giving this entire era of American history its enduring name. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Gilded_Age:_A_Tale_of_Today
Release date is 2004-06-20
Produced by David Widger
Keywords: Satire; Political fiction; Washington (D.C.) -- Fiction; Legislators -- Fiction; Speculation -- Fiction; Political corruption -- Fiction; Businessmen -- Fiction